1889 N.Y. Laws 167, ch. 140 § 1 - (:unkn) unknown (General Publisher, 1889)
Prohibited the selling or giving to a minor under the age of eighteen any pistol or other firearm. Violators guilty of a misdemeanor.
--
Keywords: TRANSFER - MINORS